Self–Directed Teacher Professional Development Influence Teachers’ Instructional - Gupta, Puja Kumari; Awasthi, Jai Raj (GS WOW: Wisdom of Worthy Research Journal, 2025)
This study investigates the impact of self-directed teacher professional development on instructional practices, focusing on teachers’ motivations, challenges, and outcomes related to self-directed learning. Using a qualitative phenomenological approach, data were collected from teachers through interviews and reflective narratives. The research explores how teachers take ownership of their professional growth to address instructional challenges and implement innovative strategies. Findings reveal that self-directed professional development fosters continuous growth, enhances instructional effectiveness, and improves student outcomes. Key motivating factors include professional aspirations and the desire to improve classroom practices. Self-directed learning also promotes teacher autonomy, creativity, and resilience by aligning professional development with real-life teaching experiences. Self-directed professional development is a dynamic and impactful approach, empowering educators and enhancing educational quality. The study’s insights are valuable for policymakers and educators aiming to cultivate a culture of continuous learning and innovation in teaching. Lessons derived from this research highlight the transformative potential of self-directed learning for effective teaching and improved student outcomes across diverse educational contexts.